Screening of School Children for Operable Congenital Heart Diseases in Dhaka city - Urmi, SJ; Rahman, MM; Alimuzzaman, M (Cardiovascular Journal, 2010)
Background: As there is no basic epidemiological study of congenital heart disease in Bangladesh, so this work was designed by the study group and was supported by Bangladesh Medical Research Council. Methods: Cross-sectional study of school going children, age ranging from 6-16 of Dhaka City were physically examined in addition to history and when required special investigation such as echocardiography was done. Results: A random sample of 5900 school-going children in the age group of 6-16 years from public and private schools of Dhaka city were screened for the prevalence of operable congenital heart diseases (CHD) during a period of 1 year. Congenital heart diseases were diagnosed, preliminary on the basis of clinical history and/or clinical examination, then confirmed by supportive investigations, such as echocardiography. Out of examined sample, 112 were found suffering from CHD, giving an overall prevalence of 19.0/1000 (16.2/1000 in boys and 22.2/1000 in girls), far greater than that of the figures recorded in available literatures for other countries. The prevalence rate was higher in girls than that of boys in the present study, which may indicate a negligence of caring towards female children in the family. In consistent, children from lower income group had a higher prevalence rate compared to their middle income group counterparts (Low income group vs middle income group: 24.5/1000 vs 13.0/1000).Poor income group had less antenatal checkup which could detect congenital heart disease earlier. Fifty three children were found to be suffering from definite operable CHD giving a prevalence of 8.98 per thousand, where, again, girls were the main victims (girls vs boys: 12.0/1000 vs 6.4/1000). Atrial septal defect was the commonest lesion 7.6%) with a prevalence of 76 per thousand followed by ventricular septal defect (4.7%) with a prevalence of 47 per thousand. Five (9.4%) cases had a family history of CHD. History of rheumatic fever and/or rheumatic heart disease were found to have a significant prevalence among cases with CHD (11.9%) as compared to children without CHD (0.9%). Conclusion: The findings of the present survey suggest the need of more frequent antenatal checkup especially in low income group large scale screening of apparently healthy children for CHD, and family members of those suffering from CHD, and that special attention be paid to the occurrence of rheumatic fever/rheumatic heart disease in cases of CHD. Key words: Congenital heart disease. DOI: 10.3329/cardio.v3i1.6422 Cardiovasc. j. 2010; 3(1): 22-25